Republic of Tanzania : Seventh Review Under the Policy Support Instrument-Press Release; Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Tanzania's Seventh Review Under the Policy Support Instrument (PSI). Program performance under the PSI has been broadly satisfactory. Most quantitative targets for June and September 2017 were met. Although progress in structural reforms has been mostly slow, efforts have been boosted to advance them. Macroeconomic policies will need to be closely coordinated. After recording a small fiscal surplus in July-September against a programmed deficit, the government is planning to step up budget implementation, particularly in development spending. The monetary policy stance and liquidity forecasting and management will need to be closely coordinated with fiscal developments. Strong growth and job creation are needed to address high poverty and a large underemployed youth population.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet